Kinerja Karyawan PT. Evercoss Technology Indonesia Semarang Dengan Komitmen Organisasi Sebagai Variabel Intervening - Triwijayanto, Herlambang; Indarto; Budiati, Yuli (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The aim of the research is to analyze the influence of Perceived Organizational Support and employee empowerment on employee performance through organizational commitment at PT. Evercoss Technology Indonesia in Semarang City. This type of research is quantitative survey research with the data source used is primary data. The population used in this research were all production employees at PT. Evercoss Technology Indonesia in Semarang City, while the research sample used was 121 respondents, and the sampling technique used simple random sampling. The data collection method uses a questionnaire, with the data analysis technique used is a Structural Equation Model (Partial Least Square (PLS). The research results show that Perceived Organizational Support and employee empowerment have a positive and significant effect on organizational commitment. Perceived Organizational Support, employee empowerment, and organizational commitment have a significant positive effect on employee performance. The results of the mediation test show that organizational commitment can significantly mediate the influence of Perceived Organizational Support and employee empowerment on employee performance.